Human esophageal myofibroblasts increase squamous epithelial thickness via paracrine mechanisms in an in vitro model of gastroesophageal reflux disease. - Liping Hu (PLoS ONE, 2020)
The pathogenesis of esophageal injury in gastroesophageal reflux disease (GERD) is incompletely understood. We modeled exposure of human esophageal myofibroblasts (HEMFs) to gastroesophageal reflux by repeated treatment with pH 4.5 and pH 4.5 bile salts and determined the effects on the epithelium in a 3D organotypic-like air-liquid interface model. Total, basal and supra-basal thickness of the epithelium were measured and immunostaining for p63, for basal (CK 14) and supra-basal (CK 4) squamous differentiation markers, and for cell proliferation (PCNA) were performed. Epithelial cell proliferation in response to HEMF conditioned media was also assessed in 2D culture. In the 3D organotypic model, total epithelial thickness increased similarly with pH 4.5 and pH 4.5 bile salt treated versus untreated and bile salt treated HEMF conditioned media. Epithelial p63 immunostaining was increased and multilayered. There was expansion of the CK14+ basal and CK4+ supra-basal layers in the epithelium established with conditioned media from pH 4.5 and pH 4.5 bile salt treated HEMFs versus untreated HEMF conditioned media. PCNA + cells per μm of tissue were unchanged in the basal layer across all treatment conditions while PCNA + cells per total DAPI + cells were decreased. In 2D culture, basal epithelial proliferation decreased with conditioned media from pH 4.5 and pH 4.5 bile salt treated HEMFs compared to conditioned media from untreated HEMF conditioned media. Secreted factors from HEMFs treated with acidic stimuli encountered in GERD increase epithelial thickness compared to secreted factors from untreated HEMFs and expand both basal and supra-basal layers. Our findings demonstrate for the first time paracrine regulation of the squamous epithelium from acid stimulated HEMFs. The effects of secreted factors from acid treated HEMFs on basal cell proliferation in this model and the mechanism mediating the increase in epithelial thickness merit further investigation.